Mutagenicity Emission Factors of Canola Oil and Waste Vegetable Oil Biodiesel: Comparison to Soy Biodiesel - DeMarini, David M. (Mutat Res, 2019)
Canola (or rapeseed) oil and waste vegetable oil (WVO) are used commonly to make biodiesel fuels composed completely from these oils (B100) or as blends with petroleum diesel (B0). However, no studies have reported the mutagenic potencies of the particulate matter with diameter ≤2.5 μm (PM(2.5)) or the mutagenicity emission factors, such as revertants/MJ(thermal) (rev/MJ(th)) for these biodiesel emissions. Using strains TA98 and TA100 with the Salmonella (Ames) mutagenicity assay, we determined these metrics for organic extracts of PM(2.5) of emissions from biodiesel containing 5% soy oil (soy B5); 5, 20, 50, and 100% canola (canola B5, B20, B50, B100), and 100% waste vegetable oil (WVO B100). The mutagenic potencies (rev/mg PM(2.5)) of the canola B100 and WVO B100 emissions were generally greater than those of B0, whereas the mutagenicity emission factors (rev/MJ(th), rev/kg fuel, and rev/m(3)) were less, reflecting the lower PM emissions of the biodiesels relative to B0. Nearly all the rev/mg PM(2.5) and rev/MJ(th) values were greater in TA98 with S9 than without S9, indicating a relatively greater role for polycyclic aromatic hydrocarbons, which require S9, than nitroarenes, which do not. In TA100 −S9, the rev/mg PM(2.5) and rev/MJ(th) for the biodiesels were generally ≥ to those of B0, indicating that most of these biodiesels produced more direct-acting, base-substitution mutagenic activity than did B0. For B100 biodiesels and petroleum diesel, the rev/MJ(th) in TA98 +S9 ranked: petroleum diesel > canola > WVO > soy. The diesel emissions generally had rev/MJ(th) values orders of magnitude higher than those of large utility-scale combustors (natural gas, coal, oil, or wood) but orders of magnitude lower than those of inefficient open burning (e.g., residential wood fireplaces). These comparative data of the potential health effects of a variety of biodiesel fuels will help inform the life-cycle assessment and use of biodiesel fuels.